Utilização de resíduo úmido de fécula de mandioca na dieta de vacas holandesas em lactação - Javorski, Cleovani Rossi (2012)
In dairy farming, one of the factors that raise the cost of production is feed, which can reach 70% of the total cost. With this, it is necessary to look for alternatives to reduce these costs without sacrificing productivity. An alternative is to enrich food resources of the animals, through the use of byproducts of industrial manioc starch. These alternative foods may constitute an interesting strategy, because in addition to being acquired by a low commercial value, may have high energy content and can also give an appropriate final destination byproduct of the cassava industry, contributing to the environment. The residue obtained during the processing of cassava has moisture content between 75% and 85%. The animal productivity can be affected negatively, depending on consumption and digestibility of nutrients. This study aimed to evaluate the chemical, microbiological, and detect the presence of mycotoxins in moist residue cassava starch (RMCS), and to evaluate the influence of five levels RMCS on intake and digestibility of nutrients, production and composition milk, and some blood parameters in dairy cows, Holstein, with average initial production of 30.65 kg milk / day. We observed a significant reduction in consumption (EE), and a linear effect for all nutrients studied, except for crude protein. Milk production was negatively affected, with a reduction to include RMCS. The chemical composition of RMCS did not change during storage, only significant variation in dry matter (DM). For populations of microorganisms, there was a significant increase only fungi and yeasts. Zearalenone levels were detected in 100% of the samples analyzed RUFM. The milk was reduced, but the efficiency of feed conversion was not affected, indicating that the residue can be used, however, it is necessary to adjust the levels of inclusion of the diet. The storage of RMCS proved effective under the conditions studied, since there were no changes in the nutritional value of the residue, but high counts of yeasts and fungi, and mycotoxins, may suggest that the material has a high risk of degradation